Effects of Ga doping on Pt/CeO2‐Al2O3 catalysts for propane dehydrogenation. Issue 12 (9th June 2016) - Wang, Tuo; Jiang, Feng; Liu, Gang; Zeng, Liang; Zhao, Zhi‐jian; Gong, Jinlong
Abstract : This paper describes catalytic consequencesThis paper describes catalytic consequences of Pt/CeO2 ‐Al2 O3 catalysts promoted with Ga species for propane dehydrogenation. A series of PtGa/CeO2 ‐Al2 O3 catalysts were prepared by a sequential impregnation method. The as‐prepared catalysts were characterized employing N2 adsorption‐desorption, X‐ray diffrtaction, temperature programmed reduction, O2 volumetric chemisorption, H2 ‐O2 titration, and transmission electron microscopy. We have shown that Ga 3+ cations are incorporated into the cubic fluorite structure of CeO2, enhancing both lattice oxygen storage capacity and surface oxygen mobility. The enhanced reducibility of CeO2 is indicative of higher capability to eliminate the coke deposition and thus is beneficial to the improvement of catalytic stability. Density functional theory calculations confirm that the addition of Ga is prone to improve propylene desorption and greatly suppress deep dehydrogenation and the following coke formation. The catalytic performance shows a strong dependence on the content of Ga addition. The optimal loading content of Ga is 3 wt %, which results in the maximal propylene selectivity together with the best catalytic stability against coke accumulation. © 2016 American Institute of Chemical Engineers AIChE J, 62: 4365–4376, 2016